Repairing a critical cranial defect using WISP1-pretreated chondrocyte scaffolds - Idan Carmon; Shira Kalmus; Anna Zobrab; Michael Alterman; Raphaelle Emram; May Gussarsky; Leonid Kandel; Eli Reich; Nardi Casap; Mona Dvir-Ginzberg (Journal of Tissue Engineering, 2023)
In cranial flat bone fractures, spontaneous bone repair will occur only when the fracture ends are in close contact. However, in cases wherein bone discontinuity is extensive, surgical interventions are often required. To this end, autologous bone is harvested and surgically integrated into the site of fracture. Here we propose to use cartilage, as an alternative autologous source, to promote cranial fracture repair. The advantage of this approach is the potential reduction in donor site morbidity, likely due to the avascular and aneural nature of cartilage. As a first step we attempted to induce cartilage mineralization in vitro, using micromass primary chondrocyte cultures, incubated with BMP2 and/or WISP1, which were examined histologically following a 3-week culture period. Next, chondrocyte seeded collagen scaffolds were evaluated in vitro for expression profiles and ALP activity. Finally, chondrocyte-seeded collagen scaffolds were implanted in a Lewis rats 8 mm critical calvaria defect model, which was imaged via live CT for 12 weeks until sacrifice. End points were analyzed for microCT, histology, and serum levels of bone related markers. Micromass cultures exhibited an osseous inducing trend following WISP1 administration, which was maintained in chondrocyte seeded scaffolds. Accordingly, in vivo analysis was carried out to assess the impact of WISP1-pretreated chondrocytes (WCS) versus untreated chondrocytes (UCS) in calvaria defect model and compared to untreated control comprised of a defect-associated blood clot (BC) or empty collagen scaffold (CS) implant. Live CT and microCT exhibited higher mineralization volumes in critical defect implanted with UCS, with some structural improvements in WCS. Histological analysis exhibited higher anabolic bone formation in WCS and trabecular bone was detected in WCS and UCS groups. Chondrocytes implanted into critical cranial defect expedite the formation of native-like osseous tissue, especially after WISP1 priming in culture. Ultimately, these data support the use of autologous chondrocytes to repair critical maxillofacial defects.